Penerapan Media Podcast (Siniar) Terhadap Keterampilan Menyimak Biografi pada Siswa Kelas X di SMKN 3 Karawang - Rizki, Nurpiyah; Sutri, Sutri; Rosalina, Sinta (Peneliti.net, 2023)
The development of information technology allows for innovation in the field of education. Podcasts as audio-based media technology can be utilized in the field of education. This study was conducted to determine whether podcast media can improve biography listening skills in class X students at SMKN 3 Karawang. The type of research used is quantitative with a Prestest-Posttest Control Group experimental research design. Class X MP 1 and MP 2 were selected as research samples with random sampling method. The results of this study indicate that Ha is accepted: the application of podcast media has an effect on improving the listening skills of class X students at SMKN 3 Karawang. This can be proven from the results of hypothesis testing for posttest data of control class and experimental class obtained Asymp. Sig (2-tailed) is 0.000, so Ha is accepted because 0.000 <0.05. In addition, the average N-gain of the experimental class is 0.77, so it is in the high category. Furthermore, the average N-gain of the control class is 0.45, so it is in the medium category. The application of podcast media to biography listening skills gets a good response from students. This can be proven from the average TCR score on all statements which is 84.82%, then the score is in the very good category.